PENGEMBANGAN MEDIA SEMPOA ABJAD UNTUK MENGEMBANGKAN KEMAMPUAN BAHASA PADA ANAK USIA 4-5 TAHUN - Samsul Mujtahidin (JURNAL ASIMILASI PENDIDIKAN, 2024)
This research is motivated by the low language skills of children at PAUD Mayang Mekar Pancor. Language skills are tools used to communicate and convey intentions, feelings and other information about something to others that can be used through writing, sound, something heard, seen and read to be conveyed to others. This study aims to develop the alphabetic abacus media to develop language skills in children and to determine the effectiveness of the alphabetic abacus media on the development of language skills in children aged 4-5 years at PAUD Mayang Mekar Pancor in the 2022/2023 learning year. This study uses 10 Borg and Gall development models which are simplified into 6 stages, namely research and data collection, planning, initial product development, initial field trials, product revisions, and field implementation tests. The type of research used in this research is Pre-Experimental Design with the type of One Group Pretest-Posttest. The research subjects were 10 children of group A PAUD Mayang Mekar Pancor. The instruments used to collect data are in the form of validation sheets and observation sheets. In addition, it can also be seen from the results of the t-count hypothesis test that is 13.33 with the t- table value of 2.262, the t-count value (13.33) > ttable (2.262). So it can be concluded that the alphabetic abacus media is effectively used to develop language skills in children aged 4-5 years at PAUD Mayang Mekar Pancor.